Legal Force of the State’s Official Publication Media: A Comparative Analysis of the Lembaran Negara and Berita Negara in the Promulgation of Legal Norms in Indonesia - Wulandari, Risa Jaya; Yusa, I Gede (IJBLE Scientific Publications Community Inc., 2025)
This study examines the differing positions and functions of the Lembaran Negara Republik Indonesia (LNRI) and the Berita Negara Republik Indonesia (BNRI) as the state’s official media for the publication of legal norms, as well as the juridical implications of these differences for the binding force of legal norms. The background of this research is rooted in the disparity of publication media used for legal products that are hierarchically equivalent, such as statutes promulgated in the LNRI and Constitutional Court decisions that are announced only in the BNRI. This situation raises concerns regarding legal certainty, the effectiveness of legal norms, and the equality of access to legal information for the public. This research employs a normative legal method with statutory, conceptual, and comparative approaches. The findings show that the LNRI functions as a constitutive promulgation medium for the enactment of legislation, whereas the BNRI serves as a declarative notification medium for administrative legal documents and decisions of state institutions such as the Constitutional Court. These differences have implications for the binding force of legal norms: norms published in the LNRI acquire general binding force upon promulgation, while publications in the BNRI emphasize transparency and accessibility without creating new legal norms. The study concludes that although LNRI and BNRI have complementary roles, inconsistencies in selecting the appropriate publication medium may weaken legal certainty and the effectiveness of law enforcement. Therefore, a revision of the national legal publication system is necessary to ensure greater integration and consistency, thereby strengthening the principles of the rule of law, information transparency, and legal certainty